Pengaruh Model Pembelajaran Cooperative Learning Berbantu Media Power Point pada Hasil Belajar Bahasa Indonesia Kelas V SD Negeri 5 Tanjung Batu - M. Shobri Aswin; Idris, Muhammad; Notosutanto Arhon Dhony, Nugroho (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The low learning outcomes in Indonesian language subjects among fifth-grade students at SD Negeri 5 Tanjung Batu indicate the need for more interactive and student-centered learning strategies. This study aimed to determine the effect of the Cooperative Learning model assisted by PowerPoint media on students’ Indonesian language learning outcomes. The study employed a quantitative approach using a One Group Pretest-Posttest Design. The sample consisted of 26 fifth-grade students selected through total sampling. Data were collected through tests and documentation, with pretest and posttest instruments that had been tested for validity, reliability, difficulty level, and discrimination index. Data analysis was conducted using descriptive statistics and the Paired Sample t-test with the assistance of IBM SPSS Statistics version 29.0. The findings revealed that the implementation of the Cooperative Learning model assisted by PowerPoint media had a significant effect on students’ Indonesian language learning outcomes. This result was indicated by a significance value (Sig. 2-tailed) of less than 0.05, leading to the acceptance of the alternative hypothesis and the rejection of the null hypothesis. In addition, the average posttest score was higher than the average pretest score. Therefore, the application of the Cooperative Learning model assisted by PowerPoint media effectively improved the Indonesian language learning outcomes of fifth-grade students at SD Negeri 5 Tanjung Batu.